Предмет: Алгебра,
автор: mNika1547
ВЫПОЛНИТЕ ДЕЙСТВИЯ ПОЖАЛУЙСТА!!!!
3x+1. 3+x
------- + ---------
x+1. x+1
3x. x+8
------ + -------
x-4. 4-x
5x+1. 6
------- - ------
x-1. x-1
iosiffinikov:
условие непонятно
Ответы
Автор ответа:
3
3x+1. 3+x 3x + 1 + 3 + x 4x + 4 4(x + 1)
------- + --------- = ----------------------- = ------------ = --------------- = 4
x+1. x+1 x + 1 x + 1 x + 1
------------------------------------------------------------------------------------------------------
3x. x+8 3x x + 8 3x - x - 8 2x - 8 2(x - 4)
------ + ------- = ---------- - ----------- = --------------- = ------------ = ------------ = 2
x-4. 4-x x - 4 x - 4 x - 4 x - 4 x - 4
--------------------------------------------------------------------------------------------------
5x+1. 6 5x + 1 - 6 5x - 5 5(x - 1)
------- - ------ = ----------------- = ------------- = --------------- = 5
x-1. x-1 x - 1 x - 1 x - 1
------- + --------- = ----------------------- = ------------ = --------------- = 4
x+1. x+1 x + 1 x + 1 x + 1
------------------------------------------------------------------------------------------------------
3x. x+8 3x x + 8 3x - x - 8 2x - 8 2(x - 4)
------ + ------- = ---------- - ----------- = --------------- = ------------ = ------------ = 2
x-4. 4-x x - 4 x - 4 x - 4 x - 4 x - 4
--------------------------------------------------------------------------------------------------
5x+1. 6 5x + 1 - 6 5x - 5 5(x - 1)
------- - ------ = ----------------- = ------------- = --------------- = 5
x-1. x-1 x - 1 x - 1 x - 1
Автор ответа:
7
(3х + 1)/(х + 1) + (3 + х)/(х + 1) = (3х + 1 + 3 + х)/(х + 1) = (4х + 4)/(х + 1) = 4(х + 1)/(х + 1) = 4
3х/(х - 4) + (х + 8)/(4 - х) = 3х/(х - 4) + (- х - 8)/(х - 4) = (3х - х - 8)/(х - 4) = (2х - 8)/(х - 4) = 2(х - 4)/(х - 4) = 2
(5х + 1)/(х - 1) - 6/(х - 1) = (5х + 1 - 6)(х - 1) = (5х - 5)/(х - 1) = 5(х - 1)/(х - 1) = 5
3х/(х - 4) + (х + 8)/(4 - х) = 3х/(х - 4) + (- х - 8)/(х - 4) = (3х - х - 8)/(х - 4) = (2х - 8)/(х - 4) = 2(х - 4)/(х - 4) = 2
(5х + 1)/(х - 1) - 6/(х - 1) = (5х + 1 - 6)(х - 1) = (5х - 5)/(х - 1) = 5(х - 1)/(х - 1) = 5
Похожие вопросы
Предмет: История,
автор: yerkenazt
Предмет: Химия,
автор: byrnakovivan
Предмет: Биология,
автор: aleksandrapazij14
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: Rhi6